Alterações no metabolismo, VO2, na composição corporal e na força muscular após resolução de COVID-19 - Capistrano Júnior, Valden Luis Matos (2022)
Introduction. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes changes that can influence human metabolism and modify the distribution of body compartments. Objective. This study described the clinical findings of changes in resting metabolism, basal oxygen consumption (VO2), and body composition in nonhospitalized patients after being diagnosed with coronavirus disease 2019 (COVID-19). Material and Methods. Physically active patients were evaluated at a nutrition clinic, and indirect calorimetry (IC) and body composition analysis using portable ultrasound were performed. After a routine appointment, all patients were instructed to inform the staff if they tested positive for SARS-CoV-2 infection. Our sample included individuals diagnosed with COVID-19, confirmed by real-time reverse transcription polymerase chain reaction (RT-PCR), within 7 days of the routine appointment. After an average incubation period of 14–21 days, in which there was no proven transmission of disease by RT-PCR, all of the patients were re-evaluated. Results: A total of 38 volunteers (63.2% female) completed the study and were included in the analysis. The mean age of the participants was 37.3 ± 8.8 years. The correlation analysis of the differences in body composition and metabolism from the post-COVID-19 period to pre-COVID-19 period demonstrated a strong correlation, with a significant difference in the difference observed in the resting metabolic rate (RMR) and basal VO2 (r = 0.99; p < 0.0001). The comparison between pre- and post-COVID-19 stratified by sex demonstrated significant reductions in the RMR and VO2 (p < 0.0001) for both groups. Regarding body composition, there was a significant increase observed in fat mass in men (p < 0.002) and women (p < 0.01), and a significant reduction observed in fat-free mass (men: p < 0.002; women: p < 0.001) and skeletal muscle mass (men: p = 0.003; women: p < 0.0001). There was a significant difference between the change in the RMR measured by IC (p < 0.0001) and that calculated by the predictive equation of Cunningham (1980) (p < 0.0001), whereas the Harris and Benedict (1918) and Mifflin (1990) equations exhibited no difference. However, the mean difference in RMR between the post- and pre-COVID-19 calculated by the Cunningham equation was -40.4 kcal/day (95% confidence interval [CI]: -56.38 to -24.45), whereas the mean difference measured by IC was -362.3 kcal/day (95% CI: -452.7 to -271.9). Conclusion: This study describes the trends in the RMR, basal VO2, and body composition in individuals with COVID-19 who were not hospitalized from the pre-COVID-19 period to the post-COVID-19 period. A significant reduction in resting energy expenditure, basal oxygen consumption, and loss of fat-free mass and muscle mass in the post-COVID-19 period were observed in both men and women.